Forensic Linguistics: Contribution of Linguistics in Legal Context - Tira Nur Fitria (Universitas Sebelas Maret, 2024)
This research describes the contribution of linguistics in forensic linguistics, especially in a legal context. This research is library research. The analysis shows that forensic linguistics applies language analysis and linguistic theories in linguistic events involved in the legal process, including products, interactions in the judicial process, and interactions between individuals that result in certain legal impacts. Forensic linguistic analysis involves linguistic fields, including phonetics, semantics, discourse and pragmatics, stylistics, morphological, syntactical, and sociological. The important role of forensic linguistics is supporting the law enforcement process, examining counterfeit documents, detecting plagiarism/lies, and analyzing sound recordings and conversations directly and indirectly. With the ‘power’ of the analysis tool of each branch, the results and conclusions obtained by linguistics forensic experts may indicate a high level of confidence. Many legal cases occur in society, including oral or written in social media such as cases of insults, defamation, threats, fraud, bullying, criticism, mockery, instigation, slander, insults, and defamation also other cases can be solved by using a forensic linguistic perspective. These cases may be quite challenging because everyone in this field is required to have comprehensive linguistic abilities with the support of elaborative capabilities of the use of spoken language or writing.